On the value of foreign PhDs in the developing world: Training versus selection effects - Helena Barnard; Robin Cowan; Moritz Müller (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2016)
This paper compares the career effects of overseas and domestic PhD training for scientists working in an emerging economy, South Africa. Variations in scientific achievements of South African academics may arise be- cause those who attend "better" PhD programmes receive better training, but it may also be because good students select into good universities. We examine selection and training effects for four tiers of South African and two tiers of foreign universities. Those who received PhDs from universities in industrialized countries tend to be more productive than those whose PhDs were locally granted, but universities from industrialized countries do not necessarily provide better training than local universities. Pure selection effects contribute to career outcomes nearly as much as training effects. When looking at training in isolation, PhDs from top South African universities produce a similar quantity and quality research output to those from leading universities in the developed world.
urn:nbn:de:swb:90-523719
Keywords: F63; H52; I2; O15; O20; O30; 330; Scientific mobility; Doctoral studies; University evaluation; Developing country; South Africa; Technological upgrading